2014
DOI: 10.1371/journal.pone.0106913
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cells Differentially Activate and Thrive on De Novo Lipid Synthesis Pathways in a Low-Lipid Environment

Abstract: Increased lipogenesis is a hallmark of a wide variety of cancers and is under intense investigation as potential antineoplastic target. Although brisk lipogenesis is observed in the presence of exogenous lipids, evidence is mounting that these lipids may adversely affect the efficacy of inhibitors of lipogenic pathways. Therefore, to fully exploit the therapeutic potential of lipid synthesis inhibitors, a better understanding of the interrelationship between de novo lipid synthesis and exogenous lipids and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 36 publications
(37 reference statements)
8
70
2
1
Order By: Relevance
“…In contrast, tumours such as ovarian cancers that grow in adipose-rich microenvironments have unconventional metabolism characterized by reduced lipogenesis and increased rates of β-oxidation (11). These observations are in line with other studies demonstrating that exogenous lipids sustain cancer cell survival when de novo lipogenesis is inhibited (33,34). It appears increasingly clear that instead of 'going through the trouble' of making their own fuel in order to proliferate, tumour cells growing in lipid-rich adipose environments take advantage of having these fuel molecules catered to them (27,35).…”
Section: Omental Adipocytes and Metabolic Effects On Tumour Cellssupporting
confidence: 83%
“…In contrast, tumours such as ovarian cancers that grow in adipose-rich microenvironments have unconventional metabolism characterized by reduced lipogenesis and increased rates of β-oxidation (11). These observations are in line with other studies demonstrating that exogenous lipids sustain cancer cell survival when de novo lipogenesis is inhibited (33,34). It appears increasingly clear that instead of 'going through the trouble' of making their own fuel in order to proliferate, tumour cells growing in lipid-rich adipose environments take advantage of having these fuel molecules catered to them (27,35).…”
Section: Omental Adipocytes and Metabolic Effects On Tumour Cellssupporting
confidence: 83%
“…Attempts to remove LPL from the system proved challenging, as removing it from media incited shifts in the metabolic phenotype of cells. While some variations were observed among BC cell lines, removal of lipoproteins generally induced the expression of FA and cholesterol synthesis-related genes, mirroring the metabolic plasticity observed by Daniels and coworkers in prostate cancer cells [52].…”
Section: Discussionsupporting
confidence: 63%
“…Our findings have implications for the development of cancer therapeutics aimed at lipid metabolism. We and others have shown that cancer cells display increased sensitivity to FA synthesis inhibitors when cultured in lipid-reduced or lipoprotein-depleted media [5,[51][52][53]. It has likewise been demonstrated that cancer cells may adjust their relative reliance on FA synthesis vs. lipolysis/uptake in response to external factors, such as nutrient availability [52].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, the critical enzymes of fatty acid biosynthesis are commonly up regulated in cancer cells (Kuhajda 2000, Vazquez-Martin, Colomer et al 2008, Daniëls VW., Smans K. et al 2014). We have previously shown extensive de novo synthesis of complex lipids from glucose in the tamoxifen-resistant MCF-7 variant LCC2 cell line (Lane, Fan et al 2009).…”
Section: Resultsmentioning
confidence: 99%